Opinions and Concerns Surrounding Long-Acting Injectable (LAI) and Oral HIV Pre-exposure Prophylaxis (PrEP) Among Current and Former LAI and Oral PrEP Users. - Schaack, Alice K.; Allamong, Maxwell B.; Hung, Frances; Barfield, Richard T.; Wilson, Sarah M.; Watkins, Tina; Link, Katherine; McKellar, Mehri S. (AIDS & Behavior, 2025)
Long-acting injectable (LAI) pre-exposure prophylaxis (PrEP) has potential to increase PrEP uptake and adherence. However, most studies investigating opinions about LAI PrEP were done prior to its approval. We administered a cross-sectional electronic survey to clients at an urban PrEP clinic in the U.S. South. Eligible participants were 18 + and had previously taken or been prescribed oral or LAI PrEP. They were asked their opinions on PrEP, barriers to access, perceived HIV risk, and PrEP stigma. Between January and April 2024, 123 people participated. Twenty-two (17.9%) used LAI PrEP, 80 (65.0%) oral PrEP, and 21 (17.1%) were not currently using PrEP. Most participants identified as men (87.8%), and mean age was 38.6 (range 19–78). Participants were 52.8% White, 27.6% Black, and 14.6% Latinx. 56.1% preferred injection versus daily oral pill. Common concerns about PrEP included side effects (n = 48), cost of medication (n = 21), and cost of clinic visits/tests (n = 21). Of those taking oral PrEP, 56.3% reported remaining on oral because LAI was not offered to them and/or they were not aware of it. Perceived HIV risk scores were on average higher for those not currently taking PrEP (not on = 26.8, SD = 6.54; LAI = 22.3, SD = 6.45; oral = 24.2, SD = 6.13). Overall, participants had low to moderate PrEP stigma scores. Despite majority preference for LAI PrEP, patients are frequently unaware of or not offered LAI. Common concerns about PrEP include side effects and costs. These data demonstrate the importance of improving LAI PrEP awareness and accessibility of choice.